(untitled) (Bangladesh Journal of Child Health, 2013)
Background: Vesicoureteric reflux is the most common urinary tract anomaly affecting the children which predisposes to higher rates of urinary tract infection and renal scarring than those without VUR. Objective: To find out the associations of VUR in children presented with UTI. Methodology: This cross sectional study was conducted in 36 children aged 1 month to 16 years who were admitted due to UTI in the Pediatric Nephrology Department of Bangabandhu Sheikh Mujib Medical University (BSMMU) from July 2009 to June 2010. UTI were evaluated by urinalysis, culture and sensitivity test, ultrasonography of the urinary system with post-voidal residue and micturating cystourethrogram subsequently. Results: This study revealed that UTI were most frequent in boys (P<0.001). Maximum number 19(52.7%) of UTI cases were detected between 12 months -60 months age group of children. Highest number of bilateral hydronephrosis 7(71.43%) and VUR 12(63.15%) were also detected in the were detected in 2-23 months age group of children. Maximum number of 22/38 kidneys (57.90%) with refluxing units were detected between 12 months to 60 months (1-5 years) age group and out of this 16(72.72%) units are of severe grades. Conclusion: Children presented with UTI along with features of obstructive- uropathy must be investigated early and carefully for VUR to prevent recurrent UTI and renal damage. DOI: http://dx.doi.org/10.3329/bjch.v37i2.17264 BANGLADESH J CHILD HEALTH 2013; VOL 37 (2) : 79-84